Plate and Shell Structures : Selected Analytical and Finite Element Solutions /: Selected Analytical and Finite Element Solutions. (2016) - Radwańska, Maria; Stankiewicz, Anna; Wosatko, Adam; Pamin, Jerzy
No abstract available